Effects of carbon monoxide, carbon dioxide, and methane on nickel/yttria-stabilized zirconia-based solid oxide fuel cells performance for direct coupling with a gasifier. (24th August 2015) - Lebreton, M.; Delanoue, B.; Baron, E.; Ricoul, F.; Kerihuel, A.; Subrenat, A.; Joubert, O.; Le Gal La Salle, A.
Abstract This work focuses on the role of CO and CO2 usually present in syngas generated by biomass gasification when they are flowed in a Ni-YSZ-based SOFC. Polarization, power versus intensity and electrochemical impedance spectroscopy measurements are performed and the theoretical aspect is enhanced with comparison with values of the Nernst potentials of the two H2O/H2 and CO2/CO couples. The CO as electrochemical reactant is clearly highlighted, and also compared to H2. Indeed, power density values of 460 mW cm−2 and 540 mW cm−2 are obtained at 750 °C when the cell is fueled with a 50% CO–50% N2 mixture and a 50% H2–50% N2 mixture respectively, and the use of CO leads to higher power density values when the percentage of the fuel in the Fuel/N2 mixture is lower than 27%, the use of higher amounts of CO inducing a large increase of the total resistance of the cell. The impact on the efficiency of the cell of the presence of CH4 is also examined using electrochemical measurements. Finally, power density values of 502 mW cm−2 is obtained at 750 °C when the cell is fueled with a 50% N2-20% CO-17% H2-10% CO2-3% CH4 mixture which appears to a be a realistic composition corresponding to the exhaust of the gasifier.